Factoring Difference of Squares

4x ^{2} - 9 = ( 2x - 3 ) ( 2x + 3 )Fill in the missing term. x ^{2} - 16 = ( x - 4 ) ( x + 4 )Fill in the missing term. x ^{2} - 4 = ( x - 2 ) ( x + 2 )Fill in the missing term. 9x ^{2} - 4 = ( 3x - 2 ) ( 3x + 2 )Fill in the missing sign. x ^{2} - 36 = ( x - 6 ) ( x + 6 )Fill in the missing terms. x ^{2} - 36 = ( x - 6 ) ( x + 6 )Fill in the missing terms. 4x ^{2} - 81 = ( 2x - 9 ) ( 2x + 9 )Fill in the missing terms. 4x ^{2} - 81 = ( 2x - 9 ) ( 2x + 9 )Fill in the missing terms. 16x ^{2} - 25 = ( 4x - 5 ) ( 4x + 5 )Fill in the missing terms. 16x ^{2} - 25 = ( 4x - 5 ) ( 4x + 5 )Fill in the missing terms. 4x ^{2} - 25 = ( 2x - 5 ) ( 2x + 5 )Fill in the missing terms. 4x ^{2} - 25 = ( 2x - 5 ) ( 2x + 5 )Fill in the missing terms. 4x ^{2} - 25 = ( 2x - 5 ) ( 2x + 5 )Fill in the missing terms. 9x ^{2} - 64 = ( 3x - 8 ) ( 3x + 8 )Fill in the missing terms. 9x ^{2} - 64 = ( 3x - 8 ) ( 3x + 8 )Fill in the missing terms. 9x ^{2} - 64 = ( 3x - 8 ) ( 3x + 8 )Fill in the missing terms. 9x ^{2} - 64 = ( 3x - 8 ) ( 3x + 8 )Fill in the missing terms. x ^{2} - 64y^{2} = ( x - 8y ) ( x + 8y )Fill in the missing terms. x ^{2} - 64y^{2} = ( x - 8y ) ( x + 8y )Fill in the missing terms. x ^{2} - 64y^{2} = ( x - 8y ) ( x + 8y )Fill in the missing terms. x ^{2} - 64y^{2} = ( x - 8y ) ( x + 8y )Fill in the missing terms. |

Students who took this test also took :

Created with That Quiz —
a math test site for students of all grade levels.